Síntese, estudo cinético e análise microestrutural do sistema cério-níquel obtido pelo método pechini - Chaves, Alexsandra Cristina (2008)
The cerium oxide has a high potential for use in removing pollutants after combustion, removal of organic matter in waste water and the fuel-cell technology. The nickel oxide is an attractive material due to its excellent chemical stability and their optical properties, electrical and magnetic. In this work, CeO2-NiO- systems on molars reasons 1:1(I), 1:2(II) e 1:3(III) metal-citric acid were synthesized using the Pechini method. We used techniques of TG / DTG and ATD to monitor the degradation process of organic matter to the formation of the oxide. By thermogravimetric analysis and applying the dynamic method proposed by Coats-Redfern, it was possible to study the reactions of thermal decomposition in order to propose the possible mechanism by which the reaction takes place, as well as the determination of kinetic parameters as activation energy, Ea, pre-exponential factor and parameters of activation. It was observed that both variables exert a significant influence on the formation of complex polymeric precursor. The model that best fitted the experimental data in the dynamic mode was R3, which consists of nuclear growth, which formed the nuclei grow to a continuous reaction interface, it proposes a spherical symmetry (order 2 / 3). The values of enthalpy of activation of the system showed that the reaction in the state of transition is exothermic. The variables of composition, together with the variable temperature of calcination were studied by different techniques such as XRD, IV and SEM. Also a study was conducted microstructure by the Rietveld method, the calculation routine was developed to run the package program FullProf Suite, and analyzed by pseudo-Voigt function. It was found that the molar ratio of variable metal-citric acid in the system CeO2-NiO (I), (II), (III) has strong influence on the microstructural properties, size of crystallites and microstrain network, and can be used to control these properties